Phosphorus pentoxide as a cost-effective, metal-free catalyst for ring opening polymerization of ε-caprolactone. Issue 39 (19th June 2020) - Adoumaz, Ismail; Boutriouia, El Hassan; Beniazza, Redouane; Qayouh, Hicham; El Kadib, Abdelkrim; Khoukh, Abdel; Save, Maud; Lahcini, Mohammed
Abstract : The ring-opening polymerization (ROP) of ε-caprolactone (ε-CL) using phosphorus pentoxide (P2 O5 ) as a metal-free catalyst and isopropanol (iPrOH) as initiator resulted in the preparation of poly(ε-caprolactone) with narrow weight distribution. Abstract : The ring-opening polymerization (ROP) of ε-caprolactone (ε-CL) using phosphorus pentoxide (P2 O5 ) as a metal-free catalyst and isopropanol (iPrOH) as initiator resulted in the preparation of poly(ε-caprolactone) with narrow weight distribution. NMR spectroscopy analyses of the prepared PCL indicated the presence of the initiator residue at the end of the polymer chain, implying the occurrence of the ε-CL-catalysis ROP through a monomer activation mechanism. Kinetic experiments confirmed the controlled/living nature of ε-CL ring-opening catalyzed by phosphorus pentoxide. The commercial availability of phosphorus pentoxide and its easy-handling provide additional opportunities for polymer synthesis and nanocomposite manufacturing.